Qualitative Study Of Maintenance Of Wooden Structures Of Traditional Houses In Damp Environments - Khotimah (Innovative Research in Civil and Environmental Engineering, 2025)
This study investigates the emerging trends and technologies transforming civil and environmental engineering in the era of digitalization and sustainability. Using a mixed-method approach that combines literature review, case study analysis, and expert surveys, the research identifies three dominant areas of innovation: digital transformation through Building Information Modeling (BIM), Internet of Things (IoT), and Artificial Intelligence (AI); sustainable construction practices using green materials and renewable energy systems; and resilience-oriented design to address climate change challenges. The findings reveal that these technologies significantly enhance project efficiency, safety, and environmental performance while promoting data-driven decision-making and proactive risk management. Statistical analysis shows a strong correlation between technology adoption and improved project outcomes in cost, time, and ecological impact. Despite notable progress, challenges such as high implementation costs, limited digital skills, and policy gaps persist. The study concludes that future civil and environmental engineering must integrate digital tools, sustainability principles, and interdisciplinary collaboration to achieve resilient and environmentally responsible infrastructure systems.